Rethinking the Green Economy in Flores: A Dialectical Approach between Deep Ecology of Spinozism and Barong Wae Tradition of the Manggaraian People - Tan, Petrus; Kosat, Oktovianus; Turu, Fransiskus Evanodius Roing (Institut Filsafat dan Teknologi Kreatif Ledalero, 2025)
In recent years, Flores has become a frontier due to government policies that exploit living space, culture, and the rights of local communities. It represents the irony of the government's policy called the Green Economy as a model of development that emphasizes common prosperity without destroying the environment and culture. This research aims to respond further to this issue by proposing a dialectic between the deep ecology of Spinozism and the Barong Wae ritual of the Manggaraian people. The method used in this research is a dialectic approach of the Principle of Expression (critical study of literature) and the Principle of Differentiation (interview key informants). This research indicates that the normative concept of the green economy is inadequate for the sustainability of local communities in Flores. It requires a radical transformation in the human paradigm of nature, creating a green cognitive, followed by green affective, and green psychomotor. The dialectic between the deep ecology of Spinoza and the Barong Wae ritual can encourage this radical paradigm by providing some key concepts, including the intrinsic values of all entities, biosphere egalitarianism, self-realization, and ecological communitarianism. It can be concluded that talking about the green economy is not only about pro-people and pro-profit, but especially pro-ecology.Keywords: Deep Ecology, Spinozism, Barong Wae, Green Economy, Ecological Communitarianism